Imaging Shapes of Objects Using Ultrasonic Waves - Hartanto (Journal Basic Science and Technology, 2022)
Image visualization is very much needed in a study. To obtain this visualization, it can be done in various ways. One of them is by utilizing ultrasonic waves to represent the shape of an object. In this paper, it will be revealed how a signal or ultrasonic wave can be converted into data in the form of a visualization display that can be understood by humans. Imaging the shape of objects using ultrasonic waves is a short analysis of how ultrasonic waves through signal processing can produce data, which in this case is an image. The yarn* system design used is a combination of hardware and software UrLrin,fS , Ultrasonic Transmitter and Receiver, MC68HC908GP32 microcontroller, MC74HC595A shift register, PPI 8255 interface and uepeIr^tn^0mpUter Se6an^^ The software used is \VinIDE_GP32 and Borland C++ Builder version 4. This system starts working when the microcontroller gets a response from the computer. The microcontroller will function as a system controller and data processor. The data obtained from the ultrasonic receiver is then processed to be converted into grayscale color. The data is then sent to the computer via the MC74HC595A and PPI 8255. The final image results are obtained by rearranging the data based on the order of pixels!. In this study the object used as a reflective object is a toy candle in the form of a block. cubes, spheres and prisms. The ultrasonic firing distance is selected 2cm, 5cm and 9cm. The final image obtained is a 2D image with a canvas size of 10 x 10 pixels and a gray scale image sharpening technique.